Does IVF-ET Procedure Increase the Pregnancy Rates in Women Underwent Laparoscopic Endometriosis Surgery? - Gürhan Güney; Aytekin Tokmak; Ali İrfan Güzel; Turgut Var; Esra İşçi; Ali Sertaç Batıoğlu (Medical Network, 2016)
OBJECTIVE: To evaluate pregnancy rates in women who underwent In Vitro Fertilization-Embryo Transfer (IVF-ET) following laparoscopic endometriosis surgery and to assess the success of IVF-ET. STUDY DESIGN: One hundred forty-one primary infertile patients who underwent laparoscopic endometriosis surgery were included in this retrospective study. After the surgery, the patients were followed up for one to eight years, and 95 patients who did not conceive postoperatively underwent IVFET (study group). RESULTS: The pregnancy rate in the study group was 35.8 % and 32.6% in the laparoscopic surgery only group (p>0.05). The total conception rate (45.4 %) within the first 12 months after laparoscopy with or without IVF was higher than in the other periods (p<0.001). In women with stage III and IV of endometriosis, the pregnancy rate was lower than the stage I and II group. Moreover, the fecundity rate in women older than 35 years was statistically significantly lower than women under the age of 35 years (p=0.003). CONCLUSIONS: In this study, the pregnancy rate was higher in the laparoscopic endometriosis surgery and IVF-ET group compared with the surgery only group, but difference was not statistically significant. Therefore, after surgery IVF-ET may be recommended to women with endometriosis related infertility.